Retinal detachment with multiple macrocysts in Stickler syndrome: case report and review of the literature - Liu, Guina; Hu, Ming; Cai, Chengcheng; Jiang, Xiaoshuang; Lu, Fang (Frontiers in Medicine, 2024)
Background Stickler syndrome is a hereditary connective tissue disorder associated with ocular, orofacial, musculoskeletal, and auditory impairments. Key symptoms encompass myopia, retinal detachment, hearing loss, and midface underdevelopment. In clinical practice, it is relatively rare to encounter retinal detachment with multiple macrocysts in Stickler syndrome. Case Presentation We report the case of a 7-year-old child who initially presented at our institution with a history of bilateral high myopia and macular coloboma in right eye. Two years subsequent to his initial presentation, he developed a rhegmatogenous retinal detachment (RRD) in the right eye, accompanied with multiple peripheral macrocysts. The detachment was successfully surgically repaired with vitrectomy, retinal laser photocoagulation, cryotherapy and silicone oil tamponade. During the operation, a mini-retinectomy in the outer layer of each macrocyst was made for vesicular drainage and retinal reattachment. Genetic testing identified a pathogenic point mutation variant (c.1693C>T; p.Arg565Cys) in exon 26 of the COL2A1 gene. Six months post-operation, the retina remained attached with improvement of best corrected visual acuity to 20/200. Conclusions Patients with Stickler syndrome may develop various presentations of RRD. The presentation of multiple macrocysts is a rarity in the existing literature on Stickler syndrome. In this case report, we share our experience in treating with multiple macrocysts in RRD and emphasize the importance of regular follow-up for patients with Stickler syndrome.